The Comparison Of Product Placement Effectiveness Between Human Influencers and Virtual Influencers - Cokki; Saraswati Hazain (Jurnal Manajemen, 2025)
This study aims to analyze the influence of attitudes toward human and virtual influencers on attitudes toward product placement and brands. The study employs a post-test experimental design without a control group, involving 287 participants: 136 participants are human, and 151 participants are virtual influencers. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) and Partial Least Squares Multigroup Analysis (PLS-MGA). The treatment in this study involved Instagram content from a human influencer and a virtual influencer. The results show that attitudes toward both human and virtual influencers positively influence attitudes toward the brand. However, attitudes toward influencers only positively influence attitudes toward product placement in the case of virtual influencers. While there is no difference in effectiveness between humans and virtual influencers in influencing attitudes toward the brand, virtual influencers are more effective in influencing attitudes toward product placement.